Affective literature, effective literacy: a case of “affect turn” among preservice teachers in Spain10/Literatura afectiva, alfabetización efectiva: un caso de “affect turn” entre futuro profesorado en España - Elena Guichot-Muñoz; Giulia De Sarlo (Tejuelo: Didáctica de la Lengua y la Literatura)
Abstract: Emotional education is an area increasingly highlighted by legislation; nevertheless, the teaching of emotions does not seem to find its rightful place in the curriculum for preservice teachers. This lack is particularly noticeable in the context of the teaching of language and literature, despite the fact that in this field the role of emotions has been recognised as crucial for decades, at least on a theoretical level. This study proposes a replicable and functional intervention in the teaching of emotions as a springboard for affective and effective literacy in preservice primary school teachers’ curriculum. The pedagogical tools used are analysed and the scope of their application is studied in a group of 66 students of the BAin Primary Education at the University of Seville, examining their impact through a triangulation of data (ad-hoc questionnaire and an evaluation of students’ learning diaries). The results showed that the intervention facilitated the link between affective and cognitive perspectives and created the need to claim a new type of multimodal, artistic, and collaborative literacy in the teaching and learning of L1, as an instrument of knowledge and self-knowledge.